A Bibliometric Analysis of the Use of Augmented Reality Technology in Enhancing Cultural Tourism Experience - Loso Judijanto; Brian Sebastian Salim (Westscience Press, 2024)
This paper presents a bibliometric analysis of augmented reality (AR) technology in the enhancement of cultural tourism experiences. By examining literature from 1999 to 2024, this study maps the scholarly terrain, identifying pivotal themes and assessing the growth trajectory of AR in cultural tourism. The research employs systematic data collection and analysis methods, including keyword co-occurrence, citation patterns, and trend analysis, to highlight the integration of AR in cultural heritage sites and its impact on the tourism industry. A particular focus is given to the shift from technological foundations to user-centric adoption and acceptance of AR. The main findings reveal a well-established focus on